The partnership the making of Goldman Sachs - Ellis, Charles D. (Penguin Press, 2008)
With unparalleled access to the firm's leadership, Ellis chronicles the brilliant individuals who built one of the world's largest investment banks.
Includes bibliographical references (p. [689]-709) and index
Keywords: Goldman, Sachs & Co; Goldman Sachs; Geschichte; Investment banking -- United States; USA